Influence of Sources and Meteorology on Surface Concentrations of Gases and Aerosols in a Coastal Industrial Complex - Allen, Andrew G. [UNESP]; McGonigle, Andrew J. S.; Cardoso, Arnaldo Alves [UNESP]; Machado, Cristine M. D. [UNESP]; Davison, Brian; Paterlini, Willian C. [UNESP]; da Rocha, Gisele O.; de Andrade, Jailson B. (Soc Brasileira Quimica, 2009)
Industrial emissions are a notorious source of atmospheric pollution in the Cubatao industrial park of Southern Brazil, where dispersion is restricted by surrounding mountain ranges. It is shown here that road transport is also a large source of gases and aerosols, which can dominate pollutant concentrations at ground level, depending on meteorological conditions. SO(2) was released mainly by industry, while road transport was a major source of NO(x). Rapid removal of NO(2) and SO(2) was attributed to fast gas phase and heterogeneous reactions, respectively. Average PM(10) concentrations increased by an order of magnitude during sea breeze fumigation, and high particulate pollution events were associated with vehicular activity. It is demonstrated that fast-response portable instrumentation can provide a useful alternative to measurements at fixed network sites for spatial (horizontal and vertical) mapping of atmospheric pollutants.
Keywords: NO(2); SO(2); PM(10); industry; transport; meteorology